ICT and collaborative co-learning in preschool children who face memory difficulties. (October 2015) - Drigas, Athanasios; Kokkalia, Georgia; Lytras, Miltiadis D.
Highlights: The effectiveness of ICT in the education of pre-schoolers is considered important. Collaborative learning in kindergarten children with the support of ICT is crucial. Memory problems can be assessed with the assistance of new technology. Pre-school and special education in terms of the co-learning needs more research. Abstract: Recent development in the role of education in pre-school children includes the use of Information and Communication Technologies (ICTs). ICT nowadays is considered as a tool that can foster the knowledge and the collaborative co-learning for this crucial age and the support of specific areas in kindergarten according to the educational perspective and the areas of needs they serve, is thought important. In this study we present a brief overview of the most representative studies of the last decade (2003–2014), which concentrates on the collaborative co learning and other ICT applications in kindergarten children who face memory difficulties. The effectiveness of ICT in literature, in maths and in children who face learning difficulties is examined. Additionally, the effectiveness of collaborative intervention and diagnostic tools for children with poor working memory in kindergarten children is examined. Concluding, this review, points out certain technological breakthroughs of several researches that focus on the support of children with such deficits.